Case Report: Associated Ocular Adverse Reactions With Inactivated COVID-19 Vaccine in China - Pang, Kunpeng; Pan, Lijie; Guo, Hui; Wu, Xinyi (Frontiers in Medicine, 2022)
Vaccine is still the best clinical measure for effective prevention and control of COVID-19. The vaccine associated ocular adverse reactions should be noted in detail among the medical community. We reported twelve eyes of 9 patient presented at Department of Ophthalmology, Qilu Hospital of Shandong University from March to August 2021 with ocular complaints following COVID-19 vaccination. The main inclusion criterion was the development of ocular symptoms within 14 days after receiving a dose of an inactivated COVID-19 vaccine. The mean (SD) age was 44.7±16.5 years (range, 19-78 years). Seven (77.8%) cases were female. The mean time of ocular adverse events was 7.1 days (range, 1-14 days) after receiving the inactivated COVID-19 vaccine. One patient was diagnosed with choroiditis, 1 with uveitis, 4 with keratitis, 1 with scleritis, 1 with acute retinal necrosis and 1 with iridocyclitis. Although the causal relationship between vaccines and ocular adverse events can’t be established from this case series report, physicians should pay attention to the ocular adverse reactions following the COVID-19 vaccine administration.